From one body to another: The handling of the deceased during the COVID-19 pandemic, a case study in France and Switzerland. (25th November 2021) - Clavandier, Gaëlle; Berthod, Marc-Antoine; Charrier, Philippe; Julier-Costes, Martin; Pagnamenta, Veronica
Abstract : The COVID-19 pandemic has brought about an unprecedented global crisis. To limit the spread of the virus and the associated excess mortality, states and governing bodies have produced a series of regulations and recommendations from a health perspective. The funerary aspects of these directives have reconfigured not only the ways in which the process of dying can be accompanied, but also the management of dead bodies, impacting on the dying, their relatives and professionals in the sector. Since March 2020, the entire process of separation and farewell has been affected, giving rise to public debates about funeral restrictions and the implications for mourning. We carried out a study in France and Switzerland to measure the effects of this crisis, and in particular to explore whether it has involved a shift from a funerary approach to a strictly mortuary one. Have the practices that would normally be observed in non-pandemic times been irrevocably altered? Does this extend to all deaths? Has there been a switch to an exclusively technical handling? Are burial practices still respected? The results of the present study pertain to the 'first wave' of spring 2020 and focus on the practices of professionals working in the funeral sector.